2014
DOI: 10.1074/jbc.m114.570200
|View full text |Cite
|
Sign up to set email alerts
|

A Type 1 Cholecystokinin Receptor Mutant That Mimics the Dysfunction Observed for Wild Type Receptor in a High Cholesterol Environment

Abstract: Background: Type 1 CCK receptor function is affected by a high cholesterol environment. Results: The CCK1R Y140A mutant has ligand binding and activation characteristics similar to wild type CCK1R in high cholesterol. Conclusion: This mutant mimics CCK1R structure in high cholesterol. Significance: This mutant represents a powerful and unique tool for identification of ligands to correct the abnormal conformation of CCK1R in high cholesterol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 56 publications
2
49
0
Order By: Relevance
“…The CCK1R has been shown to be particularly sensitive to the cholesterol composition of the lipid bilayer [50, 51]. Membrane cholesterol elevated to levels reported in metabolic syndrome [52, 53], result in functional uncoupling of CCK binding from CCK-stimulated biological activity [50, 5456]. In contrast, the closely-related CCK2R is not sensitive to this lipid [55, 56].…”
Section: Allosteric Modulation Of Endogenous Agonist Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CCK1R has been shown to be particularly sensitive to the cholesterol composition of the lipid bilayer [50, 51]. Membrane cholesterol elevated to levels reported in metabolic syndrome [52, 53], result in functional uncoupling of CCK binding from CCK-stimulated biological activity [50, 5456]. In contrast, the closely-related CCK2R is not sensitive to this lipid [55, 56].…”
Section: Allosteric Modulation Of Endogenous Agonist Actionmentioning
confidence: 99%
“…Membrane cholesterol elevated to levels reported in metabolic syndrome [52, 53], result in functional uncoupling of CCK binding from CCK-stimulated biological activity [50, 5456]. In contrast, the closely-related CCK2R is not sensitive to this lipid [55, 56]. This functional difference for structurally-related GPCRs that bind and are activated by CCK with similar high affinity and potency is an ideal setting to utilize chimeric CCK1R/CCK2R constructs to explore the molecular basis for this difference.…”
Section: Allosteric Modulation Of Endogenous Agonist Actionmentioning
confidence: 99%
“…55,56 In these studies, the impact of the cholesterol was reproduced, with elevated cholesterol resulting in higher-affinity CCK binding and lower signaling responsiveness to CCK (Figure 1). 56 This was shown to be specific to the CCK1R, with the CCK2R being resistant to the deleterious effects of cholesterol.…”
Section: Impact Of Membrane Cholesterol On Cck1r Structure and Functionmentioning
confidence: 99%
“…Indeed, this was done and it showed that this pocket was in a different conformation than either the agonist or antagonist pockets in a normal membrane. 55 This raised the extremely interesting possibility that unique drugs would have to be developed for this situation.…”
Section: Impact Of Membrane Cholesterol On Cck1r Structure and Functionmentioning
confidence: 99%
See 1 more Smart Citation